Innovations in percutaneous nephrolithotomy. (December 2016) - Tailly, Thomas; Denstedt, John
Abstract: Technical innovations in all aspects of percutaneous nephrolithotomy have changed the field considerably. The current review is aimed at reporting on the most recent advancements in the field of percutaneous nephrolithotomy. Improvements in CT imaging and the possibility of 3D rendering have dethroned the intravenous pyelogram as gold standard for pre-operative imaging. Where gaining access in the lower pole in prone position with telescopic metal dilators, placing a 30F tract used to be standard, the plethora of alternatives provides the trained surgeon with a large armamentarium to tackle any obstacle. Novel lithotripters appear more efficient than their predecessors and with tubeless PCNL gaining some momentum, ambulatory PCNL is slowly but surely becoming feasible rather than fictional. Highlights: Non contrast CT remains gold standard for PCNL. 3D reconstructions may be useful. Prone, supine or variation thereof depends on patient and surgeon preference. Accurate needle placement is key in PCNL, new techniques may improve outcomes. Ultrasound, pneumatic, combo or laser each have their place in stone disintegration. Tubeless PCNL is feasible, but remains underused. QoL of DJ vs tube is questioned.